Gaps in the ethical governance of pharmaceutical clinical trials in Europe - Bernabe, Rosemarie D. L. C.; Dawkins-Cox, Shereen A.; Gispen-de Wied, Christine C. (Frontiers in Medicine, 2025)
The ethical governance of pharmaceutical clinical trials in Europe, particularly under Regulation 536/2014, is intended to ensure the safety, rights, and well-being of participants. Despite this regulatory framework, significant gaps in ethical oversight remain. This paper identifies five key deficiencies: (1) European regulations only partially address ethical imperatives set by international guidelines, thereby restricting the ethical mandate of relevant entities; (2) the role of research ethics committees is largely limited to pre-approval activities, reducing continuous oversight during trials; (3) GCP inspectors operate within a narrow scope regarding ethical oversight, which limits their ability to identify a broad range of unethical practices; (4) there is insufficient transparency and collaboration between RECs and regulators, specifically GCP inspectorates, leading to fragmented oversight; and (5) there is minimal integration of ethical findings into the marketing authorization decision process by entities such as clinical assessors and the CHMP. To bridge these gaps, the paper suggests a shift from a prospective ethics review to a comprehensive end-to-end model of ethical governance.